2017
DOI: 10.1016/j.seizure.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Sleep abnormalities in juvenile myoclonic epilepsy—A sleep questionnaire and polysomnography based study

Abstract: JME is associated with poor sleep quality and altered architecture, irrespective of treatment status. REM sleep is significantly decreased in JME patients. Epileptiform discharges are frequent in lighter NREM sleep and EDI is higher in drug naïve patients. Although AEDs disrupt the NREM sleep, their use is associated with arousal stability in lighter stages of sleep and lower EDI, in particular with valproate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
(51 reference statements)
6
23
0
Order By: Relevance
“…(16) Similar results not distinguishable between drug-naive and valproate-groups were shown by Ramachandraiah and colleagues: higher epileptiform discharges in N1/REM in the drug-naive group; higher Table 2.…”
Section: Dosesupporting
confidence: 74%
See 4 more Smart Citations
“…(16) Similar results not distinguishable between drug-naive and valproate-groups were shown by Ramachandraiah and colleagues: higher epileptiform discharges in N1/REM in the drug-naive group; higher Table 2.…”
Section: Dosesupporting
confidence: 74%
“…(16) Sleep instability (difficulties in initiation and maintenance of sleep) in JME patients was confirmed in many studies. According to research by P.Kristian et al, (19) which was confirmed by others, (16) patients had reduced sleep efficiency, increased sleep onset latency, and increased wake percentage. Reduced REMS was noted by S.Roshan up to the total lack of REMS at all during sleep cycles.…”
Section: Psgmentioning
confidence: 91%
See 3 more Smart Citations